Preparation method of high-entropy alloy EBSD sample
Through the methods of electric spark wire cutting, grinding, electrolytic polishing and ultrasonic cleaning, high-quality high-entropy alloy EBSD samples were prepared, which solved the problems of cumbersome sample preparation process, high cost and unsatisfactory results in the prior art, and achieved high efficiency , low-cost sample preparation.
Patent Information
- Application Number
- CN202411605401.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
The existing high-entropy alloy EBSD sample preparation method has problems such as cumbersome sample preparation process, high cost and unsatisfactory effect, especially the difficulty in determining the electrolytic solution and parameters in the electrolytic polishing method.
The high-entropy alloy sample to be made was cut using an electric spark wire cutting equipment. After grinding and electrolytic polishing, combined with ultrasonic cleaning and blow-drying steps, high-quality high-entropy alloy EBSD samples were prepared.
The sample preparation process is simplified, the sample preparation speed and success rate are improved, the sample preparation cost is reduced, and the high-quality surface is obtained. The original sample calibration rate of EBSD samples reaches more than 95%.
Smart Images

Figure CN119470515A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material sample preparation, and particularly relates to a method for preparing a high entropy alloy EBSD sample. Background Art
[0002] High entropy alloys are multi-principal solid solution alloys formed by 5 or more elements in equal or nearly equal atomic ratios. Due to the good uniformity and stability of the material, it exhibits higher strength, high-temperature oxidation resistance and corrosion resistance than traditional alloys, and is widely used in aerospace, energy, electronics, medical and other fields. The phase distribution, grain orientation and texture characteristics of high entropy alloys have a significant impact on the performance of the material. EBSD technology can statistically and measure the above information due to its high angular resolution and comprehensive data characterization method.
[0003] At present, the commonly used EBSD sample preparation methods include vibration polishing, electrolytic polishing, and ion polishing. Before vibration polishing, the sample must be mounted and mechanically polished. The vibration polishing time is long and the sample preparation process is cumbersome. The ion polishing equipment cost and sample preparation cost are high, and the sample preparation efficiency is relatively low. Electrolytic polishing can effectively remove the deformation layer on the sample surface by electrochemical action, with short preparation time and low sample preparation cost. However, it is difficult to determine the conditions such as the electrolytic solution and electrolytic parameters used for electrolytic polishing for different treatment objects, resulting in unsatisfactory electrolytic polishing effect, wasted time, and increased polishing cost. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a high entropy alloy EBSD sample in view of the deficiencies of the above-mentioned prior art. The method prepares a high entropy alloy EBSD sample by grinding a cut high entropy alloy sample to be prepared, electrolytically polishing it, and ultrasonically cleaning and drying it, thereby simplifying the preparation method, improving the sample preparation speed and the sample preparation success rate, reducing the sample preparation cost, and obtaining a high entropy alloy EBSD sample with a high-quality surface, thus filling the gap in the sample preparation method of the high entropy alloy EBSD sample.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a high entropy alloy EBSD sample, characterized in that the method comprises the following steps:
[0006] Step 1: Cut the high entropy alloy sample to be made using an electric spark wire cutting device;
[0007] Step 2: polish the high entropy alloy samples prepared in step 1 with 150 mesh, 600 mesh, and 1000 mesh water sandpaper to remove the surface oxide layer generated by wire cutting;
[0008] Step 3: construct an electrolytic polishing device using a power supply, an electrolytic cell, an electrolyte, an electrode plate, and a magnetic stirrer, and then use a direct current power supply to electrolytically polish the high entropy alloy sample to be prepared after being polished in step 2;
[0009] Step 4: Use an ultrasonic cleaner to clean the high entropy alloy sample after electrolytic polishing in step 3, and blow dry it with a hair dryer to obtain a high entropy alloy EBSD sample.
[0010] The above-mentioned method for preparing a high entropy alloy EBSD sample is characterized in that the side length or diameter of the surface to be observed in the high entropy alloy sample to be prepared in step 1 is less than 20 mm, and the height of the high entropy alloy sample to be prepared perpendicular to the surface to be observed is 5 mm to 10 mm. The side length or diameter is limited to facilitate the electrolytic polishing operation, and the height is limited to ensure that the sample height requirement of the EBSD testing equipment is met.
[0011] The above-mentioned method for preparing a high entropy alloy EBSD sample is characterized in that in step 2, the surfaces to be observed in the high entropy alloy sample to be prepared are polished using 150 mesh, 600 mesh, and 1000 mesh water sandpaper respectively, and the remaining surfaces are polished flat using 150 mesh water sandpaper.
[0012] The above-mentioned method for preparing a high entropy alloy EBSD sample is characterized in that the voltage working range of the electrolytic polishing in step 3 is 30V to 50V, and the current working range is 0.5A to 2.5A. The present invention controls the voltage and current of the electrolytic polishing to ensure that the deformation layer on the surface of the high entropy alloy is fully removed to obtain an ideal high entropy alloy EBSD sample.
[0013] The above-mentioned method for preparing a high entropy alloy EBSD sample is characterized in that the electrolytic cell in step three is a cylindrical electrolytic cell made of polypropylene, and the diameter×height is Φ10cm×10cm.
[0014] The above-mentioned method for preparing a high-entropy alloy EBSD sample is characterized in that, in the electrolytic polishing device described in step three, the electrolytic cell is located directly above the magnetic stirrer, the magnetic rotor of the magnetic stirrer is located at the bottom of the electrolytic cell, and the rotation speed of the magnetic rotor during the electrolytic polishing process is 100r / min to 300r / min.
[0015] The above-mentioned method for preparing a high entropy alloy EBSD sample is characterized in that the electrolyte described in step 3 is a mixed solution of perchloric acid and ethanol with a mass content of 5% to 12%. In the electrolyte of the present invention, perchloric acid can selectively dissolve the tiny protrusions on the surface of the high entropy alloy material as an oxidant, that is, the anions generated by the decomposition of perchloric acid during electrolysis combine with the metal ions in the high entropy alloy to form a thin salt film, which is attached to the surface of the high entropy alloy sample to be made. With the progress of electrolysis and stirring, the dissolved products of the salt film diffuse into the electrolyte, thereby improving the surface flatness and brightness of the high entropy alloy sample to be made; the ethanol in the electrolyte acts as a corrosion inhibitor to increase the viscosity of the electrolyte, reduce the conductivity, and effectively prevent the surface of the high entropy alloy sample to be made from over-corrosion during the electrolysis process, and at the same time promotes the improvement of the surface brightness of the high entropy alloy sample to be made.
[0016] The above-mentioned method for preparing a high entropy alloy EBSD sample is characterized in that the cathode of the electrode plate in step three is a titanium plate, and the anode is a polished high entropy alloy sample to be prepared.
[0017] The above-mentioned method for preparing a high entropy alloy EBSD sample is characterized in that the cleaning vibration frequency of the ultrasonic cleaner described in step 4 is 30 kHz and the vibration time is 5 minutes.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] 1. The present invention grinds the cut high entropy alloy sample to be prepared, performs electrolytic polishing, and ultrasonically cleans and blows dry to obtain a high entropy alloy EBSD sample. The preparation method is simple, the sample preparation speed is fast, the sample preparation success rate is high, and the EBSD sample original pattern calibration rate is more than 95%.
[0020] 2. Compared with the vibration polishing method, the sample preparation method of the present invention does not require mounting and mechanical polishing, and has high sample preparation efficiency and Kikuchi pattern calibration rate; compared with ion polishing, the sample preparation method of the present invention has low equipment requirements and low sample preparation cost.
[0021] 3. The present invention arranges a magnetic stirrer in the electrolytic polishing device, controls the flow rate of the electrolyte by adjusting the rotation speed of the magnetic rotor, and further controls the rate of peeling of electrolytic corrosion products on the surface of the sample to be treated, so that the rate at which the electrolytic corrosion products are deposited on the sample surface and the rate at which they are detached from the surface reach a dynamic balance, thereby avoiding the thick electrolytic corrosion products adhering to the sample surface and being difficult to remove through subsequent cleaning, and increasing the amount of electrolyte.
[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1It is a structural diagram of the electrolytic polishing device of the present invention.
[0024] Figure 2 This is the grain orientation distribution diagram of the AlCoCrFeNi2.1 alloy EBSD sample prepared in Example 1 of the present invention.
[0025] Figure 3 This is the grain orientation distribution diagram of the CrAlTiNiVSi alloy EBSD sample prepared in Example 2 of the present invention.
[0026] Figure 4 This is the grain orientation distribution diagram of the FeCoNiCrMn alloy EBSD sample prepared in Example 3 of the present invention.
[0027] Description of Reference Numerals
[0028] 1—power supply; 2—electrolyzer; 3—electrolyte;
[0029] 4—electrode plate; 5—magnetic stirrer; 6—magnetic rotor. DETAILED DESCRIPTION
[0030] like Figure 1 As shown, the electrolytic polishing device of the present invention comprises an electrolytic cell 2 containing an electrolyte 3, the electrolytic cell 2 is located directly above a magnetic stirrer 5, a magnetic rotor 6 of the magnetic stirrer 5 is located at the bottom of the electrolytic cell, an electrode plate 4 is placed in the electrolyte 3, and the electrode plate 4 is connected to a power source 1. Typically, the electrolytic cell 2 is a cylindrical electrolytic cell made of polypropylene, and has a diameter×height of Φ10cm×10cm.
[0031] Example 1
[0032] This embodiment includes the following steps:
[0033] Step 1: Use electric spark wire cutting equipment to cut a rectangular AlCoCrFeNi2.1 high entropy alloy sample with a length × width × height of 20 mm × 10 mm × 5 mm;
[0034] Step 2: The 20 mm × 10 mm surface to be observed of the AlCoCrFeNi2.1 high entropy alloy sample to be prepared in step 1 is polished with 150 mesh, 600 mesh, and 1000 mesh water sandpaper respectively, and the remaining surface is polished flat with 150 mesh water sandpaper to remove the surface oxide layer generated by wire cutting;
[0035] Step 3: Build an electrolytic polishing device using a power supply, a cylindrical electrolytic cell, an electrolyte, an electrode plate, and a magnetic stirrer, and the cylindrical electrolytic cell is filled with 200 mL of electrolyte. The titanium plate is used as the cathode of the electrode plate and fixed above the cylindrical electrolytic cell with a clamp, and the distance between the titanium plate and the magnetic rotor is controlled to be 1 cm. The AlCoCrFeNi2.1 high entropy alloy sample to be processed after being polished in step 2 is used as the anode of the electrode plate, and the distance between the titanium plate and the magnetic rotor is controlled to be 2 cm. Then, a DC power supply is used to electropolish the AlCoCrFeNi2.1 high entropy alloy sample to be processed after being polished in step 2. The electrolytic polishing voltage is 48 V, the current is 2.4 A, the electrolytic polishing time is 60 s, and the speed of the magnetic rotor during the electrolytic polishing process is 100 r / min; the electrolyte is a mixed solution of perchloric acid and ethanol with a mass content of 12%;
[0036] Step 4: Use an ultrasonic cleaner to clean the AlCoCrFeNi2.1 high entropy alloy sample after electrolytic polishing in step 3. The cleaning vibration frequency is 30 kHz and the vibration time is 5 min. Blow dry with a hair dryer to obtain an AlCoCrFeNi2.1 high entropy alloy EBSD sample.
[0037] The AlCoCrFeNi2.1 high entropy alloy EBSD sample prepared in this embodiment was subjected to EBSD testing, and the obtained grain orientation distribution diagram is shown in FIG. Figure 2 As shown, from Figure 2 It can be seen that the original calibration rate of the EBSD sample is 95.2%.
[0038] Example 2
[0039] This embodiment includes the following steps:
[0040] Step 1: Use electric spark wire cutting equipment to cut a rectangular CrAlTiNiVSi high entropy alloy sample with a length × width × height of 10mm × 10mm × 5mm;
[0041] Step 2: The 10 mm × 10 mm observation surface of the CrAlTiNiVSi high entropy alloy sample to be prepared in step 1 is polished with 150 mesh, 600 mesh, and 1000 mesh water sandpaper respectively, and the remaining surface is polished flat with 150 mesh water sandpaper to remove the surface oxide layer generated by wire cutting;
[0042] Step 3: Build an electrolytic polishing device using a power supply, a cylindrical electrolytic cell, an electrolyte, an electrode plate, and a magnetic stirrer, and the cylindrical electrolytic cell is filled with 200 mL of electrolyte. The titanium plate is used as the cathode of the electrode plate and fixed above the cylindrical electrolytic cell with a clamp, and the distance between the titanium plate and the magnetic rotor is controlled to be 1 cm. The CrAlTiNiVSi high entropy alloy sample to be processed after being polished in step 2 is used as the anode of the electrode plate, and the distance between the titanium plate and the magnetic rotor is controlled to be 2 cm. Then, a DC power supply is used to electropolish the CrAlTiNiVSi high entropy alloy sample to be processed after being polished in step 2. The electrolytic polishing voltage is 35 V, the current is 1.5 A, the electrolytic polishing time is 80 s, and the speed of the magnetic rotor during the electrolytic polishing process is 180 r / min; the electrolyte is a mixed solution of perchloric acid and ethanol with a mass content of 10%;
[0043] Step 4: Use an ultrasonic cleaner to clean the CrAlTiNiVSi high entropy alloy sample after electrolytic polishing in step 3, and blow dry it with a hair dryer to obtain a CrAlTiNiVSi high entropy alloy EBSD sample.
[0044] The EBSD test was performed on the CrAlTiNiVSi high entropy alloy sample prepared in this embodiment, and the obtained grain orientation distribution diagram is as follows: Figure 3 As shown, from Figure 3 It can be seen that the original calibration rate of the EBSD sample is 96.8%.
[0045] Example 3
[0046] This embodiment includes the following steps:
[0047] Step 1: Use electric spark wire cutting equipment to cut a rectangular FeCoNiCrMn high entropy alloy sample with a diameter of Φ5mm and a height of Φ5mm.
[0048] Step 2: The observed surface with a diameter of 5 mm of the FeCoNiCrMn high entropy alloy sample to be prepared in step 1 is polished with 150 mesh, 600 mesh, and 1000 mesh water sandpaper respectively, and the remaining surface is polished flat with 150 mesh water sandpaper to remove the surface oxide layer generated by wire cutting;
[0049] Step 3: Build an electrolytic polishing device using a power supply, a cylindrical electrolytic cell, an electrolyte, an electrode plate, and a magnetic stirrer, and the cylindrical electrolytic cell is filled with 200 mL of electrolyte. The titanium plate is used as the cathode of the electrode plate and fixed above the cylindrical electrolytic cell with a clamp, and the distance between the titanium plate and the magnetic rotor is controlled to be 1 cm. The FeCoNiCrMn high entropy alloy sample to be processed after polishing in step 2 is used as the anode of the electrode plate, and the distance between the titanium plate and the magnetic rotor is controlled to be 2 cm. Then, a DC power supply is used to electropolish the FeCoNiCrMn high entropy alloy sample to be processed after polishing in step 2. The electrolytic polishing voltage is 30 V, the current is 0.7 A, the electrolytic polishing time is 120 s, and the speed of the magnetic rotor during the electrolytic polishing process is 300 r / min; the electrolyte is a mixed solution of perchloric acid and ethanol with a mass content of 5%;
[0050] Step 4: Use an ultrasonic cleaner to clean the FeCoNiCrMn high entropy alloy sample after electrolytic polishing in step 3, and blow dry it with a hair dryer to obtain a FeCoNiCrMn high entropy alloy EBSD sample.
[0051] The FeCoNiCrMn high entropy alloy EBSD sample prepared in this embodiment was subjected to EBSD testing, and the obtained grain orientation distribution diagram is shown in FIG. Figure 4 As shown, from Figure 4 It can be seen that the original calibration rate of the EBSD sample is 98.6%.
[0052] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a high entropy alloy EBSD sample, characterized in that: The method comprises the following steps: Step 1: Cut the high entropy alloy sample to be made using an electric spark wire cutting device; Step 2: polish the high entropy alloy samples prepared in step 1 with 150 mesh, 600 mesh, and 1000 mesh water sandpaper to remove the surface oxide layer generated by wire cutting; Step 3: construct an electrolytic polishing device using a power supply, an electrolytic cell, an electrolyte, an electrode plate, and a magnetic stirrer, and then use a direct current power supply to electrolytically polish the high entropy alloy sample to be prepared after being polished in step 2; Step 4: Use an ultrasonic cleaner to clean the high entropy alloy sample after electrolytic polishing in step 3, and blow dry it with a hair dryer to obtain a high entropy alloy EBSD sample.
2. The method for preparing a high entropy alloy EBSD sample according to claim 1, characterized in that: The side length or diameter of the surface to be observed in the high entropy alloy sample to be prepared in step 1 is less than 20 mm, and the height of the high entropy alloy sample to be prepared perpendicular to the surface to be observed is 5 mm to 10 mm.
3. The method for preparing a high entropy alloy EBSD sample according to claim 1, characterized in that: In step 2, the surfaces to be observed in the high entropy alloy sample to be manufactured are polished with 150-mesh, 600-mesh, and 1000-mesh water sandpapers, respectively, and the remaining surfaces are polished flat with 150-mesh water sandpaper.
4. The method for preparing a high entropy alloy EBSD sample according to claim 1, characterized in that: The voltage operating range of the electrolytic polishing described in step three is 30V to 50V, and the current operating range is 0.5A to 2.5A.
5. The method for preparing a high entropy alloy EBSD sample according to claim 1, characterized in that: The electrolytic cell described in step 3 is a cylindrical electrolytic cell made of polypropylene, and the diameter×height is Φ10cm×10cm.
6. The method for preparing a high entropy alloy EBSD sample according to claim 1, characterized in that: In the electrolytic polishing device described in step three, the electrolytic cell is located directly above the magnetic stirrer, the magnetic rotor of the magnetic stirrer is located at the bottom of the electrolytic cell, and the rotation speed of the magnetic rotor during the electrolytic polishing process is 100r / min to 300r / min.
7. The method for preparing a high entropy alloy EBSD sample according to claim 1, characterized in that: The electrolyte in step three is a mixed solution of perchloric acid and ethanol with a mass content of 5% to 12%.
8. The method for preparing a high entropy alloy EBSD sample according to claim 1, characterized in that: The cathode of the electrode plate described in step 3 is a titanium plate, and the anode is a polished high-entropy alloy sample to be manufactured.
9. The method for preparing a high entropy alloy EBSD sample according to claim 1, characterized in that: The cleaning vibration frequency of the ultrasonic cleaner described in step 4 is 30kHz, and the vibration time is 5min.
Citation Information
Cited By
Sample preparation method for EBSD characterization of microscopic structure of material
CN120609851A